A study of the use of ash from Aloe marlothii Berger for the control of maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) in stored maize - Achiano, K. A. (Kwaku Akoming) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.